Oxidative toxic stress and p53 level in healthy subjects occupationally exposed to outdoor air Pollution – a cross-sectional study in Iran - Rezaei Vandchali, Noushin; Koolivand, Ali; Ranjbar, Akram; Zarei, Parvin; Fathi, Mojtaba; Malekafzali, Sheida; Mollamohammadi, Nargess; Jalali-Mashayekhi, Farideh (Annals of Agricultural and Environmental Medicine, 2020)
It is suggested that air pollution exposure induces oxidative stress in the body and causes diseases. However, current evidence regarding the association of outdoor air pollution with some oxidative toxic stress (OTS) biomarkers in areas with different pollutant concentrations is equivocal. The aim of study was to investigate the adverse effects of outdoor air pollution on human health, by evaluating potential oxidative and anti-oxidative biomarkers and p53 protein levels in subjects exposed to different outdoor air pollution from two polluted and less polluted cities of Iran. In this cross-sectional study, a total of 203 healthy working men were selected from two cities. The activities of superoxide dismutase (SOD), catalase (CAT) and γ-glutamyltransferase (GGT) and the levels of malondialdehyde (MDA), total antioxidant capacity (TAC), and total oxidant status (TOS), were measured by the colorimetric method. The levels of p53 were measured by an ELISA method. The results showed a significant increase in the levels of p53 and MDA in the exposure group compared to the control group, while the activity of SOD and TAC was significantly decreased in the exposure group. No significant differences were found in activities of CAT and GGT, and levels of TOS between the two groups. The findings obtained confirmed the implication of air pollution in the development of OTS, and suggested useful biomarkers to evaluate the air pollution-induced harmful effects on human health in the polluted areas.